Thomas Wolfe - Turnbull, Andrew, 1921- (New York : Scribner, 1967)
Everything about Thomas Wolfe was outsize, extreme and in conflict. This biography, based in part on interviews and on documents owned by the Wolfe estate, emphasizes Wolfe's relationship to Aline Bernstein, his mistress, and Maxwell Perkins, his editor
Includes bibliographical references and index.
Keywords: Wolfe, Thomas, -- 1900-1938.